GDP Growth and FDI Nexus in ASEAN-5 Countries: The Role of Macroeconomic Performances - Anwar, Cep Jandi; Suhendra, Indra; Imansyah, Taufik; zahara, Vadilla Mutia; Chendrawan, Tony Santika (Universitas Negeri Semarang, 2023)
Numerous papers have examined the effect of national income on FDI using cross-country data, including in developing countries. However, few papers focus on one specific region, particularly in ASEAN developing countries. This study analyzes the effect of GDP growth on FDI in ASEAN-5 countries from 2004 to 2019. Panel data regression with fixed effect estimation was performed to document the relationship between GDP growth and FDI. Using some macroeconomic control variables, the findings demonstrated that GDP growth has a positive and significant impact on the FDI. Additionally, the effects of the currency rate, trade openness, and inflation on FDI are positive. Therefore, macroeconomic performances such as GDP growth, exchange rate, trade openness, and inflation are the main factors attracting FDI in ASEAN-5 countries.